Blooket as a Gamification Tool in Aqidah Akhlak Learning: Implications for Student Outcomes - Daud Pisba, Syauqi Musfirah; Rahmanto, Muhammad Arifin (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to examine the effect of using Blooket-based gamification media on student learning outcomes and to compare its effectiveness with Google Form media. The research method employed is a quasi-experimental design with a nonequivalent control group, involving an experimental group using Blooket media and a control group using Google Form media. Data were collected through pretest and posttest with 9 items to assess student learning outcomes. The results show that Blooket media significantly improved student learning outcomes, with a significance value of 0.000 (p < 0.05). These findings suggest that Blooket media can effectively enhance cognitive learning outcomes and can be used as an innovative alternative in gamification-based learning.